GESTIÓN DE LA COMUNICACIÓN Y SU INCIDENCIA EN LA DESINFORMACIÓN DE MEDIOS DIGITALES EN EL CANTÓN DE QUEVEDO - López Jijón, Santiago Alexander (2024)
This study examines the influence of digital media communication management on the generation and dissemination of misinformation in the canton of Quevedo. In a world where digital platforms are booming, it is essential to analyse local dynamics that present unique characteristics, especially in areas with a high use of social networks and restricted access to educational resources. The research adopts a mixed approach combining qualitative and quantitative methods to assess the effectiveness of local digital media in conveying reliable information. To do so, surveys of media consumers, interviews with members of local leadership and journalists about digital media, and a content analysis of relevant posts on social media and news websites in the canton were conducted. The findings reveal that a lack of training in fact-checking techniques and the pressure to generate content quickly are crucial factors that fuel misinformation. In addition, limited use of technological tools to effectively cross-check sources was observed, along with weak implementation of editorial policies that promote transparency and ethics. The study also reveals that local audiences are particularly vulnerable to misinformation due to low levels of digital literacy. This combination of factors creates an environment conducive to the spread of fake news, rumours and biased content, which in turn affects trust in the media and social cohesion in the community. The paper concludes with a series of proposals to improve communication management, such as training programmes for communicators, the implementation of fact-checking technologies and educational campaigns aimed at the population. These initiatives seek to strengthen the local media ecosystem and encourage a critical consumption of information in the canton of Quevedo. Through this analysis, the aim is to enrich the understanding of local dynamics of communication and disinformation, laying the groundwork for future research in similar contexts.